2015
DOI: 10.1371/journal.pone.0124106
|View full text |Cite
|
Sign up to set email alerts
|

Towards Elucidating Carnosic Acid Biosynthesis in Lamiaceae: Functional Characterization of the Three First Steps of the Pathway in Salvia fruticosa and Rosmarinus officinalis

Abstract: Carnosic acid (CA) is a phenolic diterpene with anti-tumour, anti-diabetic, antibacterial and neuroprotective properties that is produced by a number of species from several genera of the Lamiaceae family, including Salvia fruticosa (Cretan sage) and Rosmarinus officinalis (Rosemary). To elucidate CA biosynthesis, glandular trichome transcriptome data of S. fruticosa were mined for terpene synthase genes. Two putative diterpene synthase genes, namely SfCPS and SfKSL, showing similarities to copalyl diphosphate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 59 publications
4
63
0
7
Order By: Relevance
“…In a parallel series of experiments, CYP76AHs from rosemary and salvia known to accept miltiradiene as substrate were tested for their ability to use 13 R -manoyl oxide as a substrate. Transient expression of Ro CYP76AH4 (Zi and Peters, 2013), Ro FS1 and Sf FS (Božić et al, 2015) in N. benthamiana leaves able to synthesize 13 R -manoyl oxide demonstrated that Ro CYP76AH4 was able to efficiently convert 13 R -manoyl oxide to 11-oxo-13 R -manoyl, while Ro FS1 and Sf FS were able to produce 11-hydroxy manoyl oxide, in addition to 11-oxo-13 R -manoyl oxide (Figure 7).
10.7554/eLife.23001.017Figure 6.GC-MS analysis of miltiradiene-derived diterpenoids obtained by transient expression of CfCYP76AH15 in N. benthamiana  leaves.( A ) Total ion chromatograms (TIC) of extracts transiently expressing CfCXS, CfGGPPS, CfTPS1 and CfTPS3 (miltiradiene biosynthesis genes) in combination with water (-) or CfCYP76AH15 .
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a parallel series of experiments, CYP76AHs from rosemary and salvia known to accept miltiradiene as substrate were tested for their ability to use 13 R -manoyl oxide as a substrate. Transient expression of Ro CYP76AH4 (Zi and Peters, 2013), Ro FS1 and Sf FS (Božić et al, 2015) in N. benthamiana leaves able to synthesize 13 R -manoyl oxide demonstrated that Ro CYP76AH4 was able to efficiently convert 13 R -manoyl oxide to 11-oxo-13 R -manoyl, while Ro FS1 and Sf FS were able to produce 11-hydroxy manoyl oxide, in addition to 11-oxo-13 R -manoyl oxide (Figure 7).
10.7554/eLife.23001.017Figure 6.GC-MS analysis of miltiradiene-derived diterpenoids obtained by transient expression of CfCYP76AH15 in N. benthamiana  leaves.( A ) Total ion chromatograms (TIC) of extracts transiently expressing CfCXS, CfGGPPS, CfTPS1 and CfTPS3 (miltiradiene biosynthesis genes) in combination with water (-) or CfCYP76AH15 .
…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it is likely that the ability of CYP76AHs to catalyze 11-oxo-13 R -manoyl oxide has evolved convergently in these plants (Figure 11).
10.7554/eLife.23001.023Figure 11.Phylogeny of known full-length CYP76AHs.The enzymes used are listed below with their accession numbers or source of publication: Cf CYP76AH15, KT382358; Cf CYP76AH17, KT382360; Cf CYP76AH8, KT382348; Cf CYP76AH11, KT382349; Cf CYP76AH16, KT382359; Cf CYP76AH9, KT382347; Cf CYP76AH10, KT382346; Cf CYP71D381, KT382342; Ro FS1, AJQ30187 (Božić et al, 2015); Sm CYP76AH3, KR140168 (Guo et al, 2016); Ro FS2, AJQ30188 (Božić et al, 2015); Sf FS, AJQ30186 (Božić et al, 2015); Ro CYP76AH4, (Zi and Peters, 2013); Ro CYP76AH5v1, (Zi and Peters, 2013); Ro CYP76AH5v2, (Zi and Peters, 2013); Ro CYP76AH6, (Zi and Peters, 2013); Ro CYP76AH7, (Zi and Peters, 2013); Sm CYP76AH1, AGN04215 (Guo et al, 2013); Sp CYP76AH24, ALM25796 (Ignea et al, 2016a). Coleus forskohlii enzymes are indicated by a solid black triangle.
…”
Section: Discussionmentioning
confidence: 99%
“…Next to miltiradiene and abietatriene (a spontaneous oxidation product), monohydroxylated derivatives thereof were observed to accumulate (Figure b; Brückner et al ., ). Interestingly, none of these derivatives were reported in a more recent study, in which CPP synthase and miltiradiene synthase from Salvia fruticosa were combined with different P450s to produce ferruginol from miltiradiene, indicating that an additional biosynthetic step may outcompete the endogenous conversion (Božić et al ., ).…”
Section: Engineering Of (Novel) Diterpenoids In Photosynthetic Organismsmentioning
confidence: 97%
“…Due to the biological significance of carnosol, carnosic acid and tanshinones, there is increasing need for improved or alternative methods of production of these metabolites. As a result, efforts aiming to elucidate the related biosynthetic pathways has led to the identification of several enzymatic steps, not only in S. miltiorrhiza [ 24 , 25 ] but also in other species [ 26 , 27 ]. Specifically, diterpene synthases catalyzing the same enzymatic reactions with SmCDS and SmKSL have been identified in Rosmarinus officinalis [ 26 ] and in Salvia fruticosa [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, efforts aiming to elucidate the related biosynthetic pathways has led to the identification of several enzymatic steps, not only in S. miltiorrhiza [ 24 , 25 ] but also in other species [ 26 , 27 ]. Specifically, diterpene synthases catalyzing the same enzymatic reactions with SmCDS and SmKSL have been identified in Rosmarinus officinalis [ 26 ] and in Salvia fruticosa [ 27 ]. Identification of ferruginol synthase in S. miltiorrhiza , R. officinalis and S. fruticosa enabled the synthesis of ferruginol in yeast cells [ 22 , 27 ].…”
Section: Introductionmentioning
confidence: 99%